Higher Risk—Less Data: A Systematic Review and Meta-Analysis on the Role of Sex and Gender in Trauma Research - Haering, Stephanie; Schulze, Lars; Geiling, Angelika; Meyer, Caroline; Klusmann, Hannah; Schumacher, Sarah; Knaevelsrud, Christine; Engel, Sinha (Journal of Psychopathology and Clinical Science, 2024)
Women and men are at different risk for posttraumatic stress disorder (PTSD). It is unclear, however, howstudies on PTSD risk factors integrate this knowledge into their research. Moreover, the temporal development of women’s higher PTSDrisk is unknown. In this systematic reviewand meta-analysis,we examine howprospective studies on PTSD development (k= 47) consider sex and gender across four domains (samples, terminology, analyses, and reporting). Further, we differentially analyze sex/gender differences within five time intervals from 1 month to 5 years posttrauma. PTSD prevalence (OR= 1.72 [1.27–2.34]) and severity (g= 0.31 [0.09, 0.53]) were increased for women relative to men at 1 month posttrauma already, that is, at the first timepoint of a possible PTSD diagnosis. PTSD severity was elevated for women compared to men across all time intervals, but evidence for increased PTSD prevalence for women relative to men was less stable with longer follow-ups. Despite women’s higher PTSD burdens, they were clearly underrepresented in samples (68.3% male, 31.7% female participants). Only 5.0% of studies explained or described their understanding of sex and gender, and only 2.6% used sex as discovery variable, that is, investigating sex-dependent risk mechanisms. Sex and gender aspects in design, data, and discussion were considered by only one-third of studies each. Trauma research falls short of its potential to adequately consider sex and gender. Sex- and gendersensitive practices can advance rigor, innovation, and equity in psychopathology research.
Created from Fastlane, Scopus look-up
Keywords: gender; posttraumatic stress disorder; risk; sex; trauma